SINONIM VERBA РАЗГОВАРИВАТЬ/RAZGOVARIVAT’/’BERBICARA, BERCAKAP-CAKAP’ DALAM BAHASA RUSIA - Bianca Evangelista; Susi Magdalena (Universitas Negeri Surabaya, 2022)
The Russian language has many synonyms. Synonyms of words appear not only in the noun class, but also in adjectives, adverbs, and verbs. Verbs in Russian work as words that show activities or circumstances, expressed through the categories of aspect, tense, person, and mode. This article will discuss the synonym of the verb разговаривать/razgovarivat’/' to speak, to converse'. The method used is a descriptive analysis method and the data obtained from the site www.ruscorpora.com. The data will be analyzed and quoted according to the needs of the writing. The results of the analysis show that the use of synonymous verbs in Russian is distinguished by the style, situation, and meaning of the synonymous verbs themselves. Keywords: Russian language, synonym, verb